Enforcement of Environmental Criminal Law in Cases of Environmental Pollution by Corporations - Brata, Trisna Agus; Syafa’I, Imam (West Science Law and Human Rights, 2024)
The occurrence of various cases of environmental pollution is a reflection of the lack of corporate responsibility towards the environment, hence the need for environmental law enforcement. The formulation of the problem in this study is: 1). How is the enforcement of environmental criminal law against corporations after the enactment of Law Number 32 of 2009 concerning Environmental Protection and Management?; 2). What legal obstacles arise in criminal practice if corporations pollute the environment after the enactment of Law Number 32 of 2009 concerning Environmental Protection and Management? This research is normative legal research. The findings in this study show that the implementation of law enforcement is still weak, meaning that the subjective policy of law enforcement to continue criminal acts to further proceedings. Conditions like this are used as opportunities for corporations to do as they want and seek the maximum profit. Therefore, law enforcement must be firm and consistent. The main obstacles that occur in law enforcement practices faced when corporations commit environmental crimes are seven obstacles that affect the enforcement of environmental criminal law including: a). Obstacles to the Human Resource Capability of Law Enforcement is Still Limited; b). Environmental Enforcement Has Not Been a Priority; c). Obstacles to coordination between agencies in handling environmental crimes; d). Obstacles to Law Enforcement Professionalism; e). Obstacles to Facilities or Facilities that Support Law Enforcement; f). Dependence of Environmental Criminal Law Enforcement Application on Administrative Law; g). Criminal Law is still the ultimate remedium in environmental law enforcement.